The purposes of school knowledge in science in the Colombian Ministry of National Education curricular guidelines (2021)
This article aims to report on the purposes of the stated guidelines for natural sciences established by the Colombian Ministry of National Education. This is one of the categories for characterizing school knowledge in such guidelines. The project is carried out in the context of the Interinstitutional Doctorate in Education. The research was conducted according to the qualitative approach from an interpretative perspective through the case study method. The Curricular Guidelines, the Basic Standards of Competencies, and the Basic Learning Rights for the area of natural sciences and environmental education were examined through content analysis using the Atlas.ti software. The following results stand out: thecontribution of school knowledge in science for the construction of a responsible citizenship;scientific knowledge as the main referent of the purposes; the aim of developing attitudes, practices, and values; and how scientific knowledge may become the basis to continue with academic training or to face working and productive life. Finally, new research needs arise, for example, how to relate these citizen training goals to the proposed contents.